2015
DOI: 10.1021/acs.joc.5b00416
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer Emission in Oligotriarylamine–Triarylborane Compounds

Abstract: Donor-acceptor compounds exhibiting charge transfer emission are of interest in a variety of different contexts, for example, for nonlinear optical processes and for sensor applications. Recently investigated triarylamine-triarylborane compounds represent an important class of donor-acceptor systems, and we explored to what extent their charge-transfer properties can be further improved by using stronger amine donors and borane acceptors than prior studies. The oligotriarylamine employed here is a much stronge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…All the absorption maxima displayed by THHBI derivatives in various solvent are ascribed to the charge-transfer states, which can be further proved by following quantum chemical calculations results. It is found that the absorption maximum for each dye shows nearly no noticeable shift but the emission spectra show appreciable bathochromic shift with increase in polarity of solvents, indicating nearly zero dipole moment in the ground state but large dipole moments in the excited state 24 25 26 . The peak positions of absorption and emission spectra for all dyes as a function of the solvent polarity are displayed in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…All the absorption maxima displayed by THHBI derivatives in various solvent are ascribed to the charge-transfer states, which can be further proved by following quantum chemical calculations results. It is found that the absorption maximum for each dye shows nearly no noticeable shift but the emission spectra show appreciable bathochromic shift with increase in polarity of solvents, indicating nearly zero dipole moment in the ground state but large dipole moments in the excited state 24 25 26 . The peak positions of absorption and emission spectra for all dyes as a function of the solvent polarity are displayed in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…In this context the interesti n new organoboronc ompounds as fluorescent dye platforms is steadily growing with the aim to optimizea nd diversify photophysicala nd photochemical properties, such as light absorption, emission quantum yields, or photochemical stability. Three-coordinate organoboron dyes [1,2] contain electron-deficient boron.T his electronic feature introduces acceptorp roperties that may be integrated in sophisticated charge-transfer architectures [3][4][5][6][7] and two-photon-addressable molecules. [8,9] The Lewis acidic nature of trivalent boron can be used for the design of chemosensors forf luoride.…”
Section: Introductionmentioning
confidence: 99%
“…Three‐coordinate organoboron dyes contain electron‐deficient boron. This electronic feature introduces acceptor properties that may be integrated in sophisticated charge‐transfer architectures and two‐photon‐addressable molecules . The Lewis acidic nature of trivalent boron can be used for the design of chemosensors for fluoride .…”
Section: Introductionmentioning
confidence: 99%
“…6570 � 190 cm À 1 , which is comparable to other compounds with strong charge transfer properties, as well as a good linearity of the plot (R 2 = 0.9925) further support the charge transfer nature of this class of complexes. [14] Upon photoexcitation at 436 nm in degassed acetone, the complexes generally give broad and structured emission bands at ca. 557-708 nm, with lifetimes in the microsecond regime.…”
Section: Resultsmentioning
confidence: 99%